Lotions, potions, pills, and magic : health care in early America - Breslaw, Elaine G., 1932- (New York University Press, 2012)
In the years following the American Revolution, as poverty increased and America's water and air became more polluted, people grew sicker. Traditional medicine became increasingly ineffective. Instead, Americans sought out both older and newer forms of alternative medicine and people who embraced these methods: midwives, folk healers, Native American shamans, African obeahs, and the new botanical and water cure advocates. The author describes the evolution of public health crises and solutions, and argues that their ascendance over other healers didn't begin until germ theory finally migrated from Europe, and American medical education achieved professional standing. In addition to being a history of health in early America, it is a history of struggle, as natives and newcomers alike grappled with the obstacles imposed by biology, ecology, and fellow human beings. The author's position, supported by stories and anecdotes, calls for a reconsideration of the history of America, its health, and its doctors.